2021
DOI: 10.1007/s10549-021-06458-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on perceived access to health care and preferences for health care provision in individuals (being) treated for breast cancer

Abstract: Purpose To evaluate perceived access to health care and preferences for health care provision among patients (being) treated for breast cancer during the COVID-19 pandemic. Methods Longitudinal study within the prospective, multicenter UMBRELLA cohort of patients (being) treated for breast cancer. All cohort participants enrolled in UMBRELLA between October 2013 and November 2020 were sent a COVID-19-specific survey during the first and second wave of the COVID-19 pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A survey of breast cancer patients in April 2020 showed that 14.4% of patients had a higher threshold for contacting their breast cancer physician due to the pandemic, and this number decreased to 7.5% in November 2020. 49 …”
Section: Discussionmentioning
confidence: 99%
“…A survey of breast cancer patients in April 2020 showed that 14.4% of patients had a higher threshold for contacting their breast cancer physician due to the pandemic, and this number decreased to 7.5% in November 2020. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Studies reviewed in this study mentioned that it is effective [ 28 - 36 , 38 - 55 , 57 - 60 ], and it meets the digital preference of patients [ 28 - 34 , 36 - 60 ] because many patients value technology [ 28 - 31 , 33 , 34 , 36 - 60 ]. The pandemic has taught health care that telemedicine increases patients’ perception of the availability of care and most patients prefer this modality [ 68 ]. It is convenient, saves time and mileage [ 28 - 31 , 33 , 34 , 36 - 60 ], enables education at one’s own pace [ 28 , 30 , 38 , 39 , 44 , 52 , 53 ], avoids stigma [ 29 , 32 ], and provides personal navigation through the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…As no secondary procedures were performed to enhance cosmetic outcomes, we believe that our tailored approach to partial defects of the ear was successful in addressing common issues in auricle reconstruction. The selection of a single stage procedure was enthusiastically accepted by the elderly patients and, in our opinion, represents a valuable solution, especially during the COVID-19 pandemic, as it reduces patient access to hospitals [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%